FASE-family and social engagement model for prevention and management of self harm behavior–a study protocol for cluster randomized control trial in India - Devassy, Saju Madavanakadu; Scaria, Lorane; Benny, Anuja Maria; Cheguvera, Natania; Varghese, Jaicob; Joubert, Lynette (Frontiers in Psychiatry, 2022)
Abstract Background Suicide is a substantial public health concern for countries worldwide. Effective preventive and curative interventions for self-harm behaviour (SHB) are imperative for nations with an alarmingly high rate of suicide and self-harm behaviours. The intervention protocol named FASE (Family and Social Engagement) consists of comprehensive assessment, Attachment-Based Family Therapy (ABFT), and community linkages for people presenting with suicide or self-harm in emergency departments of tertiary hospitals. Methods This article reports the design and protocol for a cluster randomized control trial for suicide prevention and management. After the developed intervention is pilot tested in a tertiary hospital in Kerala, the intervention will be scaled up to be implemented in various tertiary hospitals in Kerala. Each hospital emergency department will be considered a cluster, and these clusters will be randomized to the intervention group and control group in a 1:1 ratio. The eligible people from the intervention clusters will undergo a baseline assessment, a structured moderate intense intervention with twelve sessions spread across six months by the trained social workers supervised by the Mental health team, and a follow-up assessment at the end. Participants will be recruited after obtaining consent and explaining the study. The primary outcome includes suicidality measured by the Depressive Symptom Inventory – Suicidality Subscale (DSI-SS), Depression, Anxiety and Stress Scale (DASS), MOS Social Support Survey, and Brief resilience scale (BRS). Discussion Knowledge generated from this trial can significantly affect new programmatic policy and clinical guidelines that will improve the reduction of suicide rates in the country. Trial Registration Prospectively registered in Clinical Trial Registry India (ICMR-NIMS) on 18/10/2021 (ref number- REF/2021/10/048264).